O pluralismo global de Paul Feyerabend - Luiz Henrique de Lacerda Abrahão (2015)
This thesis seeks to identify conceptual elements to grasp the theoretical unity of Paul Karl Feyerabend’s (1924-1994) philosophy. Chapter I examines a range of readings and readers of his philosophy and their disagreements. Chapter II criticizes some exegetic dogmas associated to Feyerabend’s ideas and explores the two leitmotifs of his philosophical programme of ‘Critique of Scientific Reason’: science’s structure/nature and science’s merit/excellence. Chapter III examines the different stages in Feyerabend’s intellectual development in the 1940s and 1950s focusing on the Pragmatic Theory of Observation and on the notion of Epistemic Voluntarism. Afterwards it introduces the new hermeneutic of Feyerabend’s corpus: the notion of Global Pluralism, which unrestrictedly expands the Principle of Proliferation to the domains of ideas (theoretical pluralism), actions (methodological pluralism), forms of life (cultural pluralism), and cosmovisions (ontological pluralism). Chapter IV looks into the repercussions of Feyerabend’s opposition to the monist ideal of Unity of Science for the contemporary image of science as a fragmentary practice. The Conclusion suggests humanitarian limits for values such as freedom of thought, autonomy of action, cultural diversity, and abundance of worldviews.